Soft Regulation vs. Hard Manipulative Technologies – Conceptual Foundations in Informational Governance - Takhmina Mamadaliyeva (Scientific Trends, 2025)
In the digital era, public stability is increasingly linked to the integrity and governance of the information environment. This article examines the dichotomy between “hard” manipulative technologies—such as censorship, surveillance, and disinformation—and “soft” regulation based on media literacy, transparency, and self-regulation. While hard methods may provide immediate control, they risk undermining public trust and democratic values. By contrast, soft regulation seeks to build resilient societies by empowering citizens to critically engage with information and resist manipulative content. Through a political-cultural and ideological lens, the article argues that soft informational governance not only enhances information security but also reinforces democratic legitimacy and pluralism.
Keywords: Soft regulation; information security; disinformation; political culture; censorship; media literacy; democratic governance; hard regulation; digital authoritarianism; public trust.